Review of Calling Out to Isis: The Enduring Nubian Presence at Philae - Cooper, Julien.
Solange Ashby, Calling Out to Isis: The Enduring Nubian Presence at Philae. Georgias Studies in the Ancient Near East 13. Piscataway, Georgias Press, 2020. ISBN 9781463207151. Pp. 332, 32 figures (incl. maps, plans).